Regulatory T-cell therapy in Crohn's disease: challenges and advances. Issue 5 (24th January 2020) - Clough, Jennie N; Omer, Omer S; Tasker, Scott; Lord, Graham M; Irving, Peter M
Abstract : The prevalence of IBD is rising in the Western world. Despite an increasing repertoire of therapeutic targets, a significant proportion of patients suffer chronic morbidity. Studies in mice and humans have highlighted the critical role of regulatory T cells in immune homeostasis, with defects in number and suppressive function of regulatory T cells seen in patients with Crohn's disease. We review the function of regulatory T cells and the pathways by which they exert immune tolerance in the intestinal mucosa. We explore the principles and challenges of manufacturing a cell therapy, and discuss clinical trial evidence to date for their safety and efficacy in human disease, with particular focus on the development of a regulatory T-cell therapy for Crohn's disease.